Cucumber mosaic virus pada Tanaman Lada di Yogyakarta dan Bangka Belitung - Emerensiana - Uge; sri sulandari; sedyo - hartono; susamto - somowiyarjo (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2019)
Cucumber mosaic virus on Black Pepper in Yogyakarta and Bangka BelitungPepper (Piper nigrum) is spice crop which has been cultivated a long time ago in Indonesia. Stunting is one of disease on pepper caused by cucumber mosaic virus (CMV). The research aimed to diagnose the biological, morphological and nucleaic acid characters of CMV on pepper in Yogyakarta and Bangka Belitung. CMV infection on pepper in both area (Putat dan Kleben village, Yogyakarta and Air Buluh village, Bangka Belitung) showed typical symptoms such as mosaic, narrow leaves and stunting. The disease incidence and disease severity of stunting disease are varies. The virus able to transmitted by cutting, grafting and mechanically on Nicotiana tabacum and Chenopodium amaranticolor. However, it was unable to transmitted mechanically on pepper and by Aphis gossypii. The virus particles were isometric with diameter size 28-30 nm. RT-PCR using coat protein partial gene primer successfully amplified a DNA with size ± 500 bp from all three samples. The homology of nucleotide between three isolates was 98-97%, while the highest homology of those three strains CMV from Yogyakarta and Bangka Belitung was 98% against strains from China in Brassica chinensis. Three strains CMV from pepper were in the same group, and separated from CMV pepper lines from Indonesia and other CMV isolates.